Integration of Interleukin-6 Improves the Diagnostic Precision of Metagenomic Next-Generation Sequencing for Infection in Immunocompromised Children - Wang, Di; Lai, Min; Song, Hua; Zhang, Jing-Ying; Zhao, Fen-Ying; Liang, Juan; Xu, Wei-Qun; Tang, Yong-Min; Xu, Xiao-Jun (Frontiers in Microbiology, 2022)
The performance of metagenomic next-generation sequencing (mNGS) in identifying pathogens in immunocompromised children was not very clear. The purpose of this study is to assess the performance of mNGS in this population and to investigate whether the integration of serum cytokines and mNGS assay could improve the diagnostic accuracy. We retrospectively collected the clinical data of pediatric patients who suffered febrile diseases and underwent mNGS determination simultaneously in the department of hematology/oncology between January 2019 and March 2021. Specimens were evaluated bysent for conventional microbiological test (CMT), mNGS and serum cytokine measurement in parallel. A total of 258 episodes of febrile diseases were enrolled, mNGS was positive in 224 cases, while CMT was positive in 78 cases. mNGS and CMT were both positive in 70 (27.1%) cases and were both negative in 26 (10.1%) cases. There were 154 (59.7%) cases positive by mNGS only while 8 (3.1%) were positive by CMT only. It is common that two or more pathogens were simultaneously detected by mNGS in single specimen, with only 61 tests identified a single organism. Whether the organisms reported by mNGS were the microbiological etiology of infection was evaluated. Of the 224 cases with positive mNGS results, 135 (58.4%), 30 (13.0%) and 59 (28.6%) were considered as “probable”, “possible” and “unlikely”, respectively. Patients with high IL-6 (≥390pg/mL) were likely to be bacterial infection. Although mNGS reported mixed pathogens, 84.6% (33/39) and 83.3% (10/12) of patients presenting high IL-6 were confirmed as bacterial infection in training and validation cohort, respectively. In conclusion, mNGS analysis demonstrates promising diagnostic potential in rapidly identifying clinically relevant pathogens. Given detection of many clinically irrelevant organisms, integrating integration of IL-6 improves the precision of mNGS results interpretation.